Comparison between laparoscopic and robotic surgery for sentinel lymph node mapping in endometrial cancer using indocyanine green and near infra-red fluorescence imaging. (19th May 2021) - Chaowawanit, Woraphot; Campbell, Vicki; Wilson, Emily; Chetty, Naven; Perrin, Lewis; Jagasia, Nisha; Barry, Sinead
Abstract: Indocyanine green (ICG) and near infra-red fluorescence imaging in minimally invasive surgery is an option to map sentinel lymph nodes (SLN). The aim of this study was to compare the outcomes of SLN mapping between laparoscopic and robotic surgery. One-hundred-and-forty women with histologically confirmed endometrial cancer, were treated with a minimally invasive hysterectomy, bilateral salpingo-oophorectomy and SLN mapping. After anaesthetic induction, ICG was superficially injected into cervical submucosa and deeply injected into the cervical stroma at the 3 and 9 o'clock positions (1.25 mg/site). Eleven cases were abandoned after ICG injection (laparoscopic surgery seven cases and robotic surgery four cases) because of obesity, technical difficulty and peritoneal disease. One-hundred-and-eleven patients were analysed. Seventy-six patients had a laparoscopic procedure and 33 patients had robotic surgery. The overall and bilateral detection rates were 97% and 83% for laparoscopic surgery and 88% and 73% for robotic surgery. Laparoscopic surgery was superior to robotic surgery in terms of overall detection ( p -value .046). There was no significant difference in the intra-operative SLN identification time or SLN dissection time between laparoscopy and robotic surgery ( p -value .247 and .145, respectively). Further research is required to compare laparoscopy and robotic surgery in terms of SLN detection. Impact Statement: What is already known on this subject? Sentinel lymph node (SLN) mapping aims to avoid complications and provide useful staging information for endometrial cancer. ICG has been shown to improve the detection rate and NPV compared with other tracers (blue dye and technetium 99). No data exists comparing SLN mapping rates using ICG in laparoscopy and robotic surgery. What do the results of this study add? The overall and bilateral detection rates were 97% and 83% for laparoscopic surgery and 88% and 73% for robotic surgery. Laparoscopic surgery was superior to robotic surgery in terms of overall detection. There was no significant difference in the intra-operative SLN identification time or SLN dissection time between laparoscopy and robotic surgery. What are the implications of these findings for clinical practice and/or further research? : This study confirms that laparoscopy and robotic surgery are not different in terms of bilateral detection rate and SLN operating time; the study population is small.